2019
DOI: 10.1212/wnl.0000000000007753
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy duration and seizure outcome in epilepsy surgery

Abstract: ObjectiveTo conduct a systematic review and meta-analysis on the effect of earlier or later resective epilepsy surgery on seizure outcome.MethodsWe searched the electronic databases PubMed, EMBASE, and Cochrane Library for studies investigating the association of epilepsy duration and seizure freedom after resective surgery. Two reviewers independently screened citations for eligibility and assessed relevant studies for risk of bias. We combined data in meta-analyses using a random effects model. We assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 47 publications
0
51
0
9
Order By: Relevance
“…Conversely, duration of epilepsy did not predict seizure outcome. Shorter duration of epilepsy has been associated with better outcomes in some studies 7,9,36,37 but not in others, 13,18 possibly due to different designs (longitudinal or cross‐sectional) and statistical methods. Our findings, although confirming that there is a long delay before epilepsy surgery is performed, 4,24 indicate that patients with TLE who undergo surgery in childhood are more likely to achieve sustained seizure freedom.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, duration of epilepsy did not predict seizure outcome. Shorter duration of epilepsy has been associated with better outcomes in some studies 7,9,36,37 but not in others, 13,18 possibly due to different designs (longitudinal or cross‐sectional) and statistical methods. Our findings, although confirming that there is a long delay before epilepsy surgery is performed, 4,24 indicate that patients with TLE who undergo surgery in childhood are more likely to achieve sustained seizure freedom.…”
Section: Discussionmentioning
confidence: 99%
“…Other treatment options, such as surgery, are widely considered a last resort. Sadly, the associated time delay means such treatments may be less effective 78. The result is often years of reduced quality of life, lost productivity, and increased mortality 9…”
Section: Uncertainty In Treatment Response Is Major Problemmentioning
confidence: 99%
“…Early referral of patients with drug-resistant epilepsy or with complex epilepsy syndromes (e.g., epileptic spasms [West syndrome], Dravet syndrome, continuous spikes and waves during slow sleep, tuberous sclerosis complex) is paramount to improve patients' chances to achieve seizure control and avoid impairment of neurological and cognitive development in children, irreversible psychological and social problems, [51,52] Carbamazepine Phenytoin life-long disability and premature death [57,58]. A recent systematic review showed that a shorter duration of epilepsy was significantly associated with a better seizure outcome after resective epilepsy surgery [59]. Aside from surgery, epilepsy centers can offer specialized diagnostic and therapeutic approaches that may identify the underlying cause of apparent or real drug resistance (e.g., non-adherence to medication, misdiagnosis, inadequate dosing, life style factors) and lead to seizure freedom in patients initially considered drug resistant (Fig.…”
Section: Drug-resistant Epilepsy and The Importance Of Early Referralmentioning
confidence: 99%